PENGARUH LITERASI KEUANGAN, GAYA HIDUP, DAN FINTECH PAYMENT TERHADAP MANAJEMEN KEUANGAN RUMAH TANGGA (Studi Kasus pada Ibu Rumah Tangga di Perumahan Grand Sutera Rajeg) - Rosita, Azizah Dilla; Rosyid, Rosyid; Nuraini, Luthfi (Politeknik Negeri Lhokseumawe, 2025)
Abstract: The problems that occurred in this study were the level of financial literacy of housewives which was still relatively low, the implementation of a high lifestyle, and a lack of understanding of the use of fintech payment. This study aims to determine and analyze the influence of financial literacy, lifestyle, and fintech payment on household financial management. The object of the study is in the Grand Sutera Rajeg Housing. The population of this study were all housewives in the Grand Sutera Rajeg Housing, with a sample size of 89 respondents. The sampling technique used non-probability sampling with purposive sampling technique. The data collection technique used a questionnaire. The analysis method used in this study is the multiple linear regression analysis method with the help of IBM SPSS 29. The results of this study indicate that financial literacy has a positive effect on household financial management, lifestyle has a negative effect on household financial management, and fintech payment has no effect on household financial management. Keywords: Fintech payment, lifestyle, Financial literacy, Household Financial, Management.